The effects of training based on Nordic hamstring and sprint exercises on measures of physical fitness and hamstring injury prevention in U19 male soccer players - Raya-González, J.; Martin, L. T.; Beato, M.; Rodríguez-Fernández, A.; Sanchez-Sanchez, J. (Research in Sports Medicine, 2023)
This study analysed the effects of a training program based on Nordic hamstring and sprint exercises on physical performance and hamstring injuries in young male soccer players. Forty-nine U19 players were randomly assigned to a control (CG; n = 26) or experimental group (EG; n = 23). Linear sprint and with change of direction (COD) were assessed before and after a 14-week training period. Hamstring injuries were collected during the intervention period. Between-groups analysis revealed differences in linear sprint performance (p = 0.012-0.001) in favour of the EG. Pre-to-post performance increased significantly in the EG for 20 m (effect size [ES] = -0.56) and 30 m (ES = -0.62) sprints, but a significant reduction in some COD parameters was observed (ES = 0.45-0.57). In CG, only a significant reduction in COD with dominant leg was found (ES = 0.63). Significant differences in injury burden in favour of the EG was reported such as (27.87 [CG] vs. 3.82 [EG] absence days/1000 h of exposure, rate ratio = 7.30, 95% CI 3.34-15.99). While injury incidence was not different between the EG and CG. These findings suggest that the training program implemented can improve sprint performance and reduce injury burden.